KAJIAN PUSTAKA KANDUNGAN KIMIA DAN AKTIVITAS FARMAKOLOGI BEBERAPA TUMBUHAN MARGA ARTOCARPUS - Karina Buddhisuharto, Anastasia
The Artocarpus genus from Moraceae family widely distributed in the tropical and subtropical regions of Asia, can be used as food commodity and to treat diseases. In this study, phytochemical compounds and pharmacological activities of several Artocarpus species were examined. The writing of this study was performed to elaborate phytochemical compounds and pharmacological activities of Artocarpus plants. The reference journals have DOI and were obtained through database from Scopus and PubMed website to ensure their validity and reliable contents. This literature study was made by using minimum 50 literatures from the last 10 years. Based on this study, it was known that some Artocarpus species contained abundance of flavonoids, phenols, steroids, tannins, saponins, and triterpenoids. The compounds had various activities such as antimicrobial, antifungal, antiviral, antidiabetic, anticancer, antimalarial, anti-inflammatory, and antioxidant. Hence, further studies about safety test is needed to assure that Artocarpus plants can be used as standardized herbal medicine. Further research about efficacy and safety test on clinical level can also be done.